The difference is in the start: Impact of timing and start procedure on sprint running performance - Haugen, T. A.; Toennessen, E.; Seiler, S. K. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to compare different sprint start positions and to generate correction factors between popular timing triggering methods on 40-m/40-yd sprint time. Fourteen female athletes (17 ± 1 years), personal best 100 m: 13.26 (±0.68) seconds and 11 male athletes (20 ± 5 years), personal best 100 m: 11.58 (±0.74) seconds participated. They performed 2 series of 3 40-m sprints in randomized order: (a) start from the block, measured by means of Brower audio sensor (BAS) and Dartfish video timing (DVT), (b) 3-point start, measured by using hand release pod (HR) and DVT, and (c) standing start, triggered by both photocell across starting line (SFC), and foot release (FR) plus DVT. Video analysis was performed by 2 independent observers and averaged. Simultaneous measurements at national athletics competitions demonstrated that DVT and BAS were equivalent to Omega Timing within the limits of precision of video timing (±0.01 seconds). Hand and floor timer triggering showed small but significant biases compared with movement captured from video (0.02-0.04 seconds), presumably because of sensitivity of pressure thresholds. Coefficient of variation for test-retest timing using different starting positions ranged from 0.7 to 1.0%. Compared with block starts reacting to gunfire, HR, SFC, and FR starts yielded 0.17 ± 0.09, 0.27 ± 0.12, and 0.69 ± 0.11 second faster times, respectively, over 40 m (all p < 0.001) because of inclusion or exclusion of reaction time, plus momentum, and body position differences at trigger moment. Correction factors for the conversion of 40 m/40 yd and 40 yd/40 m were 0.92 and 1.08, respectively. The correction factors obtained from this study may facilitate more meaningful comparisons of published sprint performances.